The reporting of theoretical health risks by the media: Canadian newspaper reporting of potential blood transmission of Creutzfeldt-Jakob disease - Ahmad Nadya; Dornan Christopher; Code Catherine; Wilson Kumanan; Hébert Paul; Graham Ian (BMC, 2004)
Abstract Background The media play an important role at the interface of science and policy by communicating scientific information to the public and policy makers. In issues of theoretical risk, in which there is scientific uncertainty, the media's role as disseminators of information is particularly important due to the potential to influence public perception of the severity of the risk. In this article we describe how the Canadian print media reported the theoretical risk of blood transmission of Creutzfeldt-Jakob disease (CJD). Methods We searched 3 newspaper databases for articles published by 6 major Canadian daily newspapers between January 1990 and December 1999. We identified all articles relating to blood transmission of CJD. In duplicate we extracted information from the articles and entered the information into a qualitative software program. We compared the observations obtained from this content analysis with information obtained from a previous policy analysis examining the Canadian blood system's decision-making concerning the potential transfusion transmission of CJD. Results Our search identified 245 relevant articles. We observed that newspapers in one instance accelerated a policy decision, which had important resource and health implication, by communicating information on risk to the public. We also observed that newspapers primarily relied upon expert opinion (47 articles) as opposed to published medical evidence (28 articles) when communicating risk information. Journalists we interviewed described the challenges of balancing their responsibility to raise awareness of potential health threats with not unnecessarily arousing fear amongst the public. Conclusions Based on our findings we recommend that journalists report information from both expert opinion sources and from published studies when communicating information on risk. We also recommend researchers work more closely with journalists to assist them in identifying and appraising relevant scientific information on risk.